Role of the Hippo pathway in liver regeneration and repair: recent advances - Monica Pibiri; Gabriella Simbula (BMC, 2022)
Abstract Although the signaling pathways involved in normal liver regeneration have been well characterized, less has been done for livers affected by chronic tissue damage. These "abnormal livers" have an impaired regenerative response that leads to liver repair and fibrosis. The tumor suppressor Hippo pathway plays a key role in liver regeneration and repair. On this basis, this review discusses recent studies focusing on the involvement of the Hippo signaling pathway during "normal healthy liver regeneration" (i.e., in a normal liver after 2/3 partial hepatectomy) and "abnormal liver regeneration" (i.e., in a liver damaged by chronic disease). This could be an important question to address with respect to new therapies aimed at improving impaired liver regenerative responses. The studies reported here have shown that activation of the Hippo coactivators YAP/TAZ during normal liver regeneration promotes the formation of a new bile duct network through direct BEC proliferation or/and hepatocyte dedifferentiation to HPCs which can trans-differentiate to BECs. Moreover, YAP/TAZ signaling interaction with other signaling pathways mediates the recruitment and activation of Kupffer cells, which release mitogenic cytokines for parenchymal and/or non-parenchymal cells and engage in phagocytosis of cellular debris. In addition, YAP-mediated activation of stellate cells (HSCs) promotes liver regeneration through the synthesis of extracellular matrix. However, in chronically diseased livers, where the predetermined threshold for proper liver regeneration is exceeded, YAP/TAZ activation results in a reparative process characterized by liver fibrosis. In this condition, YAP/TAZ activation in parenchymal and non-parenchymal cells results in (i) differentiation of quiescent HSCs into myofibroblastic HSCs; (ii) recruitment of macrophages releasing inflammatory cytokines; (iii) polarization of macrophages toward the M2 phenotype. Since accumulation of damaged hepatocytes in chronic liver injury represent a significant risk factor for the development of hepatocarcinoma, this review also discussed the involvement of the Hippo pathway in the clearance of damaged cells.